Metabarcoding Analysis of Ichthyoplankton in the East/Japan Sea Using the Novel Fish-Specific Universal Primer Set - Kim, Ah Ran; Yoon, Tae-Ho; Lee, Chung Il; Kang, Chang-Keun; Kim, Hyun-Woo (Frontiers in Marine Science, 2021)
Spatiotemporal distribution of the fish larvae and eggs is one of the most important information for their reproduction and recruitment in an aquatic ecosystem. We here employed the metabarcoding strategy as an alternative method for the conventional ichthyoplankton survey, which requires considerable amount of times, labors, and cost. First, a piscine-specific universal primer set (FishU) was designed to amplify the region flanking the highly conserved mitochondrial 12S and 16S ribosomal sequences, which was optimized for MiSeq platform. Based on both in-silico and in-vitro analyses, the newly designed FishU primers outperformed the two previously reported fish-specific universal primer sets (ecoPrimer and MiFish) in taxon coverage and specificity and accuracy in species identification. The metabarcoding results by FishU primers successfully presented the diversity of ichthyoplankton directly from the zooplankton net samples in the East/Japan presenting more accurate and more species numbers compared with those by MiFish primers. Despite several limitations, the metabarcoding analysis of ichtyoplankton using the newly designed FishU primers would be one of the promising tools providing many useful data to understand the reproduction of fish such as spawning sites, reproductive periods, population structures with relatively low cost and labors.